Panchayati Raj institutions 73rd Amendment - apprehensions and comprehensions. - Dhawan, G. (1995)
"Analysing the various provisions in the Act, the author says that there is need to transfer much of the allocation decisions to the local authorities as financial arrangement is the lifebreath of all self-governments. Restructuring of the education system is the only instrument for changing the attitude of the people. Involving the NGOs in the planning, training, implementation and evaluation of the rural development programmes will strengthen the Panchayati Raj institutions. The reservation of seats for women, SCs and STs needs to be addressed more seriously by the States, observes the author"
Keywords: India. Constitution - Amendments - 73rd; Panchayat - India